Education System Relationship, Education Management, With Educational Worker Satisfaction - John Eka Powa; Hapzi Ali; Kasful Anwar Us (Dinasti Publisher, 2023)
This research is a quantitative research with a survey method. The sampling technique uses a probability sampling technique with a total sample of 67 education personnel. Hypothesis testing uses path analysis with a significance level of ? = 0.05. This study resulted in ten conclusions, namely, among others: 1). There is a relationship between the education system (X1) and the job satisfaction of educational staff (Y). 2). There is a relationship between education management (X2) and educational staff job satisfaction (Y). 3). There is a relationship between the education system (X1) and education management (X2) with the job satisfaction of educational staff (Y).